Sistema Nacional de Avaliação da Educação Básica: uma leitura crítica - Santos, Regina Lucia Lourido dos (2001)
The present study has as fundamental objective the critical analysis of the National Basic Education Assessment System - S AEB - as a national assessment policy which aims to assess the quality of Brazilian education. Our criticism considered the theoretical and methodological characteristics of the System in order to perceive articulations and / or contradictions between the proposed objectives and 03 results obtained and, more, if such characteristics contribute or not to the maintenance of evaluative practices that justify social inequalities. It is a qualitative research of documentary character, using elements of the technique of content analysis, which worked, as fundamental data sources for analysis, with SAEB reports and documents prepared by System coordinators under study. The analysis was guided by the categories objective / evaluation and quality / quantity. Analyzing the data, we find inconsistencies and even contradictions between the objectives of the System and the referrals for carrying out the measurements, which seriously compromises the achieving the intended objectives. On the other hand, we perceive contradictions between the discourse quality through results assessment and an effective commitment by the State to invest under evaluation, since the reports mentioned above point more to questions of a political nature the school, disregarding the context of the elaboration of the policies that are proposed to analyze, as if the problems originated and were solved at that level of intervention.